(untitled) (Anclajes, 2021)
Going beyond an autobiographical reading of María Moreno’s Black out (2016), this article analyzes its intertextualities with late 19th century modernist novels. Moreno’s novel, set in the late 20th century, reveals thematic and formal resonances with narratives that novelized the life and times of the artist. This reading of Black out as an artist novel is based on the relationship it establishes with the modernist archive (constant similarities and also important differences), such as the newspaper form, the defense of a particular aesthetics, and the definitions and positions toward literary labor.